Parthenocarpy Fruit Formation in Cucumber (Cucumis sativus L.) with Giberelin Hormone Application on The Lowland of Palopo - Rahman Hairuddin; Nining Triani Thamrin; I Ketut Sugiarta (Universitas Sembilanbelas November Kolaka, 2019)
This study aimed to observe (1) The formation of parthenocarpy fruit in cucumber with the application of Giberelin hormone and (2) the concentration of Giberelin to form the parthenocarpy fruit on cucumber. This study was held at campus 2 trial land, Faculty of Agriculture Cokroaminoto University, Palopo. The method used in this study was group randomized design method with five treatments and three replications, i.e P0 (without Giberelin application), P1 (200 mg/L Giberelin), P2 (250 mg/L Giberelin), P3 (300 mg/L Giberelin) and P4 (350 mg/L Giberelin). The result showed that the application of Giberelin with 350 mg/L concentration (P4) significantly affected the formation of parthenocarpy fruit on the number of seed produced with 379.96 seeds. The highest number of seeds produced was observed in control treatment (P0) with 496.27 seeds. Furthermore, the fruit fresh weight, diameter, and length had no significant difference